Menerobos Wacana-Wacana Teologis Kristiani tentang Misteri Allah Tritunggal dalam Rangka Mengonstruksi Moderasi dalam Berteologi - Petrus Lakonawa (ILMU USHULUDDIN, 2017)
This paper will briefly explore the main discourses about the triune God in the development of Christian theology to propose some theological moderation about the Divine mystery which Augustine called as the beauty ever ancient but ever new and increasingly alluring. Some of the moderation approaches offered by the author in this article are first, the talk about the Triune God, though imperfect, is finally done so that those who believe in it do not remain silent about mysteries that are very close but also far transcending in their faith and life experiences. Second, ethical kriteria are needed as principles that could guide theological effort so that theologies will be able to produce positive impacts on the real life of all creation. Third, the need to be aware of the limitations of symbols, expressions, metaphors, definitions and discourses about God for God transcends human understanding (apophatic theology). Fourth, because God is a mystery beyond the reach of human understanding, therefore, it needs to be realized that no theology is absolute and monopolizing all discourses rather it is necessary to talk about God in various ways and symbols in order to complement one another. Fifth, apophatic awareness that God is incomprehensible leads to the humility of mystical theology. The study in this paper will begin by briefly describing the development of the theology of the Trinity from the Early Church to the Enlightenment, followed by critical notes and proposals developed by contemporary theologians on the discourse about the Triune God and end up with a concluding note in the form of a way of moderation in doing theology.